Synthesis, molecular modeling, and biological evaluation of novel imatinib derivatives as anticancer agents - Gunay, Fulya; Balta, Sevcan; Ng, Yuk Yin; Ulucan, Ozlem; Turgut, Zuhal; Gunkara, Omer Tahir (Tubitak Scientific & Technological Research Council Turkey, 2022)
Different derivatives of imatinib were synthesized by a 3-step reaction method. The structures of the new compounds were characterized by spectroscopic methods. For quantitative evaluation of the biological activity of the compounds, MTT assays were performed, where four BCR-ABL negative leukemic cell lines (Jurkat, Reh, Nalm-6 and Molt-4), one BCR-ABL positive cell line (K562), and one non-leukemic cell line (Hek293T) were incubated with various concentrations of the derivatives. Although imatinib was specifically designed for the BCR-ABL protein, our results showed that it was also effective on BCR- ABL negative cell lines except for Reh cell line. Compound 9 showed lowest IC50 values against Nalm-6 cells as 1.639 mu M, also the values of Compound 10 for each cell were very close to imatinib. Molecular docking simulations suggest that except for compound 6, the compounds prefer a DFG-out conformation of the ABL kinase domain. Among them, compound 10 has the highest affinity for ABL kinase domain that is close to the affinity of imatinib. The common rings between compound 10 and imatinib adopt exactly the same conformation and same type of interactions in the ATP binding site with the ABL kinase domain.
Keywords: Imatinib derivatives; tyrosine kinase inhibitors; BCR-ABL inhibitors; leukemia; anti-cancer agents; molecular docking; KINASE INHIBITOR; SELECTIVE INHIBITOR; RAF KINASE; POTENT; DISCOVERY; GROWTH; MUTANT; ACTIVATION; RESISTANCE; MORPHOLINE; Chemistry; Engineering